2012
DOI: 10.1095/biolreprod.112.104018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Constitutive Pig Ovary Heat Shock Chaperone Machinery and Its Response to Acute Thermal Stress or to Seasonal Variations1

Abstract: Reduced oocyte competence causes the lower fertility reported in domestic sows during the warm months of the year. Somatic cells express heat shock proteins (HSPs) to protect themselves from damage caused by thermal stress. HSPs are classified as molecular chaperones and control the correct folding of newly synthesized or damaged proteins. The present work performed a comprehensive survey of the different components of the heat shock chaperone machinery in the pig ovary, which included the HSP40, HSP70, HSP90,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 46 publications
5
30
1
Order By: Relevance
“…The expressions of HSP90AA1 and PTGES3 mRNAs in the ampullary oviduct were higher in summer than in winter, whereas there was no difference in them in the isthmic oviduct in summer and winter. It has been reported that the expression of HSPs is higher in porcine oocytes in summer than in winter, although there are no seasonal changes in porcine cumulus cell (Pennarossa et al 2012). Therefore, it is possible that the expressions of HSP90AA1 and PTGES3 in the isthmic oviduct are not affected by different seasonal conditions in contrast to those in the ampullary oviduct.…”
Section: Discussionmentioning
confidence: 97%
“…The expressions of HSP90AA1 and PTGES3 mRNAs in the ampullary oviduct were higher in summer than in winter, whereas there was no difference in them in the isthmic oviduct in summer and winter. It has been reported that the expression of HSPs is higher in porcine oocytes in summer than in winter, although there are no seasonal changes in porcine cumulus cell (Pennarossa et al 2012). Therefore, it is possible that the expressions of HSP90AA1 and PTGES3 in the isthmic oviduct are not affected by different seasonal conditions in contrast to those in the ampullary oviduct.…”
Section: Discussionmentioning
confidence: 97%
“…A study reported that exposure of COCs to elevated temperature increased HSP-70.1 mRNA in cumulus cells and some adverse effects of heat stress on oocytes were intervened through cumulus cells (Payton et al 2011). Besides, exposure of buffalo oocytes to elevated temperature (41.5°C) for 1 h greatly disrupted oocyte maturation and resulted in upregulation of HSP-70.1 mRNA expression at 8-to 16-cell and blastocyst (Pennarossa et al 2012). It suggests that heat stress can promote HSP-70.1 mRNA synthesis in buffalo and this could be used as marker of biological effect of heat stress in buffalo.…”
Section: Discussionmentioning
confidence: 99%
“…How exactly heat impacts female fertility is not well understood, although it most likely involves compromised production of gametes and embryos capable of development. Heat stress has been associated with reduced developmental competence, and induction of apoptosis in in vitro fertilised and parthenogenetically activated pig embryos (Isom et al 2007b;Bertoldo et al 2010;Pennarossa et al 2012). Although the heat shock protein (HSP) machinery is constitutively expressed in the somatic cells of the ovary, there is only a change in abundance in the oocyte in response to whole-ovary heat stress (Pennarossa et al 2012), suggesting that regulation in response to hyperthermia may occur within the porcine oocyte.…”
Section: Heat Stress Compromises Female Fertilitymentioning
confidence: 99%